PDP Act 2010 beyond “personal”, “data” and “protection”: how the data privacy law transforms business landscape in Malaysia and beyond - Zulhuda, Sonny (2013)
It is a sea of data out there where we can only swim or sink. There is only one better option, which is to embrace this digital growth. The process of coming to terms with this Big Data environment may not always be pleasant; often it is achieved through painful experiences at both individual and collective level. The industries who learned about this change are quickly trying to grab every possible fortune that pops up in this process. The individuals whose personal information have increasingly flooded public spaces and open network are normally the immediate receiver of the consequences. Their data are thus exploited: discreetly stored, aggregated, disclosed, exchanged for money, traded at black market or kept indefinitely.